Peran Kepala Sekolah Sebagai Entrepreneur dalam Meningkatkan Jumlah Peserta Didik di SMA Swasta Cerdas Murni - Tasya Widyana; Rustam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how the role of the principal as an entrepreneur in increasing the number of students in SMA Swasta Cerdas Murni. Specifically, this study aims to explain the form of managerial innovation and superior programs developed by the principal to improve school competitiveness, analyze external partnerships that build the principal as part of the strategy to increase the number of students, and control risks to increase the number of education students. This research method uses a qualitative approach of the case study type with observation, interview, and documentation techniques. The main respondents are the principal and vice principal who have several strategies in developing and the ability to increase the number of students in SMA Swasta Cerdas Murni. The results of the study indicate that the principal as an entrepreneur has a significant role in increasing the number of students in SMA Swasta Cerdas Murni. They show initiative by developing superior programs, collaborating with external parties, and compiling learning programs each year. The creativity of the principal is manifested in efforts to improve the quality of education and the attractiveness of prospective new students. However, the challenges faced by the principal in increasing the number of students include limited resources and competitiveness to other private schools. Therefore, this study recommends the need for support from the community and the school in supporting the principal to increase the number of students in SMA Swasta Cerdas Murni.